Cellulosic bioethanol production from empty fruit bunches by locally produced cellulases - Zainan, Nur Hidayah; Alam, Md. Zahangir; Al-Khatib, Ma An Fahmi Rashid (2011)
The global shortage of fossil fuels and environmental concerns to reduce pollution has resuscitated the interest in bioethanol production. Bioethanol is a promising alternative energy source that can be produced from renewable resources through hydrolysis and sugar fermentation processes. Its current production mainly involves fermentation of grains rich in sugar or starch and sugarcane. However, this process is not sustainable since these raw materials are needed for food and feed production. The utilization of lignocellulosic materials for bioethanol production such as empty fruit bunches (EFB) from palm oil plant attract increasing attention as an abundantly available and cheap renewable residue especially in Malaysia where palm oil production is the major agricultural industry. Conversion of EFB to bioethanol involves a three step process. Firstly, the pretreatment of lignocellulosic material followed by hydrolysis using cellulase enzyme to produce reducing sugars and the fermentation processes in the presence of suitable microorganisms. In this study, cellulase enzyme used for the hydrolysis was produced from palm oil mill effluent (POME), whose cost of production was considerably low compared to commercial cellulases. The hydrolysis of EFB for sugar production as an initial step was statistically optimized based on agitation speed, EFB and cellulase concentrations using Response surface methodology (RSM)/ Box-Behnken design in 2L Bioreactor. Maximum sugar production was realized after three days hydrolysis. The amount of sugar produced showed an economic feasibility of using EFB as a renewable raw material for bioethanol production